Implementation of the Pancasila Student Profile in Shaping the Character of Fourth-Grade Students at SD Negeri 12 Sungai Sapih - Intan Dusvia; Rica Azwar; Ayunis Ayunis; Stavinibelia Stavinibelia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe the application, supporting factors, and inhibiting factors of the implementation of the Pancasila Student Profile in character building of fourth grade students at SD Negeri 12 Sungai Sapih. The method used is descriptive qualitative with the research subjects being fourth grade teachers and four students. Data were obtained through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing stages. The results showed that the implementation of the Pancasila Student Profile was realized through daily habits, such as group prayer activities, class duty schedules, group work, and project-based learning. This implementation includes six main dimensions: faith and devotion to God Almighty and noble character, global diversity, cooperation, independence, critical reasoning, and creativity. Supporting factors for the implementation of this profile include teacher role models, consistency in habit formation, and parental involvement. Meanwhile, the obstacles encountered include a lack of consistency in student behavior, limited school facilities, and weak supervision of activities. In general, the implementation of the Pancasila Student Profile in this school has been going well, although improvements are still needed in maintaining consistency in student behavior, strengthening the role of teachers and parents, and providing more adequate facilities and infrastructure.